Continuous Inhalation Exposure to Fungal Allergen Particulates Induces Lung Inflammation While Reducing Innate Immune Molecule Expression in the Brainstem. (July 2018) - Peng, Xinze; Madany, Abdullah M.; Jang, Jessica C.; Valdez, Joseph M.; Rivas, Zuivanna; Burr, Abigail C.; Grinberg, Yelena Y.; Nordgren, Tara M.; Nair, Meera G.; Cocker, David; Carson, Monica J.; Lo, David D.
Continuous exposure to aerosolized fine (particle size ≤2.5 µm) and ultrafine (particle size ≤0.1 µm) particulates can trigger innate inflammatory responses in the lung and brain depending on particle composition. Most studies of manmade toxicants use inhalation exposure routes, whereas most studies of allergens use soluble solutions administered via intranasal or injection routes. Here, we tested whether continuous inhalation exposure to aerosolized Alternaria alternata particulates (a common fungal allergen associated with asthma) would induce innate inflammatory responses in the lung and brain. By designing a new environmental chamber able to control particle size distribution and mass concentration, we continuously exposed adult mice to aerosolized ultrafine Alternaria particulates for 96 hr. Despite induction of innate immune responses in the lung, induction of innate immune responses in whole brain samples was not detected by quantitative polymerase chain reaction or flow cytometry. However, exposure did trigger decreases in Arginase 1, inducible nitric oxide synthase, and tumor necrosis factor alpha mRNA in the brainstem samples containing the central nervous system respiratory circuit (the dorsal respiratory group, ventral respiratory group, and the pre-Bötzinger and Bötzinger complexes). In addition, a significant decrease in the percentage of Toll-like receptor 2-expressing brainstem microglia was detected by flow cytometry. Histologic analysis revealed a significant decrease in Iba1 but not glial fibrillary acidic protein immunoreactivity in both the brainstem and the hippocampus. Together these data indicate that inhalation exposure to a natural fungal allergen under conditions sufficient to induce lung inflammation surprisingly causes reductions in baseline expression of select innate immune molecules (similar to that observed during endotoxin tolerance) in the region of the central nervous system controlling respiration.